Procedural and clinical outcomes of type 0 versus type 1 bicuspid aortic valve stenosis undergoing trans-catheter valve replacement with new generation devices: Insight from the BEAT international collaborative registry. (15th February 2021) - Ielasi, Alfonso; Moscarella, Elisabetta; Mangieri, Antonio; Giannini, Francesco; Tchetchè, Didier; Kim, Won-Keun; Sinning, Jean-Malte; Landes, Uri; Kornowski, Ran; De Backer, Ole; Nickenig, Georg; De Biase, Chiara; et al.
Abstract: Background: Although bicuspid aortic valve (BAV) is not considered a "sweet spot" to trans-catheter aortic valve replacement (TAVR), a certain number of BAV underwent TAVR. Whether BAV phenotype affects outcomes following TAVR remains debated. We aimed at evaluating the impact of BAV phenotype on procedural and clinical outcomes after TAVR using new generation trans-catheter heart valves (THVs). Methods: patients included in the BEAT registry were classified according to the BAV phenotype revealed at multi-slice computed tomography (MSCT) in type 0 (no raphe) vs. type 1 (1 raphe). Primary end-point was Valve Academic Research Consortium–2 (VARC-2) device success. Secondary end-points included procedural complications, rate of permanent pacemaker implantation, clinical outcomes at 30-day and 1-year. Results: Type 0 BAV was present in 25(7.1%) cases, type 1 in 218(61.8%). Baseline characteristics were well balanced between groups. Moderate-severe aortic valve calcifications at MSCT were less frequently present in type 0 vs. type 1 (52%vs.71.1%, p  = 0.05). No differences were reported for THV type, size, pre and post-dilation between groups. VARC-2 success tended to be lower in type 0 vs. type 1 BAV (72%vs86.7%; p  = 0.07). Higher rate of mean transprosthetic gradient ≥20 mmHg was observed in type 0 vs. type 1 group (24%vs6%, p  = 0.007). No differences were reported in the rate of post-TAVR moderate-severe aortic regurgitation and clinical outcomes between groups. Conclusions: Our study confirms TAVR feasibility in both BAV types, however a trend toward a lower VARC-2 device success and a higher rate of mean transprosthetic gradient ≥20 mmHg was observed in type 0 vs. type 1 BAV. Highlights: Despite being a relative contraindication a certain number of BAV underwent TAVR. We assessed the impact of BAV type on procedural and clinical outcomes post TAVR. VARC-2 success tended to be lower in type 0 vs. type 1 BAV. higher rate of high residual gradient was observed in type 0 compared to type 1 BAV. No differences were noted in the rate of AR and clinical outcomes between BAV types.